Diagnostic dermoscopy the illustrated guide - Bowling, Jonathan (John Wiley & Sons, 2012)
"Ideal for clinic use, both for diagnosis and for explaining to the patient, this guide provides: a quick reference atlas guide to the diagnosis skin lesions, especially, but not limited to, those that are cancerous icons for each condition linked to high definition dermoscopy and clinical photographs. Real dermatoscopic images and the associated clinical photographs on the page opposite"--Provided by publisher.